Hematuria in pregnancy due to renal arteriovenous malformation: A case report - Ashie Kapoor; Leo Yamaguchi; Sherwin Azad; Yi McWhorter (Elsevier, 2021)
A 31-year-old pregnant woman at 22 weeks and 2 days of gestation presented to the emergency room with complaints of painless hematuria and passage of clots. Initial computed tomography angiography (CTA) of the abdomen and pelvis performed after ultrasound revealed evidence of blood products in the bladder. However, the CTA did not reveal any source of bleeding. Given hemodynamic instability and persistent pain, the patient was taken to the operating room for a cystoscopy, which revealed bleeding from the left renal unit, giving rise to suspicion of a renal arteriovenous malformation (AVM). The patient then underwent left renal digital subtraction angiography (DSA), which produced no evidence of active bleeding. Due to high clinical suspicion and ongoing symptomatic hematuria, she underwent DSA a second time, which did demonstrate renal AVM bleeding, and embolization was performed. This case highlights the importance of cystoscopy in diagnosing a renal AVM in a pregnant patient despite the risks of general anesthesia during pregnancy.